Pendampingan Pengembangan Media Pembelajaran Berbasis Artificial Intelligence bagi Ustaz Digital Pondok Pesantren di Poncokusumo Malang - Arief Ardiansyah; Bahroin Budiya; Mukhammad Naafiu Akbar (Jurnal Pemberdayaan Masyarakat, 2026)
This community service program aimed to enhance the pedagogical capacity of Islamic boarding school teachers in Poncokusumo, Malang, by integrating artificial intelligence (AI)-based learning media to support Arabic language instruction. The implementation adopted a Community-Based Participatory Research (CBPR) approach, involving stages of needs assessment, joint planning, practical assistance, and participatory evaluation. A total of 15 participants from 10 pesantren took part in the training, which focused on developing interactive media using ChatGPT and Kahoot as the main platforms. The results indicated that most participants rated the training materials as systematic, relevant to their profession, and effective in increasing their knowledge of modern educational technology. However, some challenges remained, particularly in technical understanding and the need for more time for independent practice. Overall, the program proved effective in providing practical skills and motivation for teachers to innovate in their teaching practices. Future sustainability of the program is expected through follow-up training and more intensive technical support, enabling pesantren to deliver adaptive, creative, and digitally aligned learning experiences.